BUDAYA KERJA SENTRA PELAYANAN KEPOLISIAN TERPADU (SPKT) POLSEK MARON PADA PELAYANAN PENERIMAAN PENGADUAN PUBLIK - Tri Pepri; Suwandono Suwandono; Intisari Intisari; Anung Budiranto; Ika Tyas N; Yuyun Istifarida; Dicky Perdana Putra; Zuhdan Kurnia Gusti; Puji Wanusta Rini; Arif Liyantono; Nurul Qomariah (Relawan Jurnal Indonesia, 2026)
This study aims to analyze the work culture of the Integrated Police Service Center (SPKT) of Maron Sector Police in handling public complaints. The research employed a qualitative approach, with data collected through field observations, in-depth interviews with residents and community leaders in Maron Village, Brani Wetan Village, and Satreyan Village, as well as documentation. The findings indicate that the work culture of the SPKT of Maron Sector Police in administrative services has been implemented fairly well and has provided tangible benefits to the community. However, the work culture in handling criminal complaints has not yet been optimal, as evidenced by the lack of follow-up actions, low responsiveness, and limited transparency regarding case progress information. These conditions have contributed to a decline in public trust in police services. Analysis based on the organizational culture theories of Edgar H. Schein and Robbins & Judge reveals that the work culture of the SPKT of Maron Sector Police remains predominantly procedural and administrative in nature, but has not been fully internalized into the values and underlying assumptions of excellent public service. This study concludes that improving the quality of police services requires strengthening a work culture that is responsive, professional, transparent, and problem-solving oriented in order to enhance public trust.